2019
DOI: 10.35371/aoem.2019.31.e10
|View full text |Cite
|
Sign up to set email alerts
|

Association between depression and cardiovascular disease risk in general population of Korea: results from the Korea National Health and Nutrition Examination Survey, 2016

Abstract: BackgroundDepression is considered as a risk factor for cardiovascular disease (CVD) and associated with changes in individuals' health status that might influence CVD risk. However, most studies have scrutinized this relationship on a rather narrower and specific study population. By focusing on general population of Korea, we sought to inspect the association of depression with CVD risk and cardiovascular risk factors.MethodsThe data from the first year (2016) of the 7th Korea National Health and Nutrition E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…A study involving patients having experienced heart failure has showed that the PHQ-9 is effective in identifying depressive symptoms (Bhatt et al, 2016). In addition, the PHQ-9 has been widely used in many depression studies on patients with cardiovascular disease (Ludwig et al, 2018; Song et al, 2019; Suzuki et al, 2016). The Cronbach alpha in this study for this assessment was 0.899.…”
Section: Methodsmentioning
confidence: 99%
“…A study involving patients having experienced heart failure has showed that the PHQ-9 is effective in identifying depressive symptoms (Bhatt et al, 2016). In addition, the PHQ-9 has been widely used in many depression studies on patients with cardiovascular disease (Ludwig et al, 2018; Song et al, 2019; Suzuki et al, 2016). The Cronbach alpha in this study for this assessment was 0.899.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores mean higher depression (Kroenke et al, 2001). In addition, many studies have confirmed that PHQ-9 is an effective tool for the study of depression in patients with CVDs (Ludwig et al, 2018;Song et al, 2019;Suzuki et al, 2016). The Cronbach's coefficient alpha was 0.90.…”
Section: Participantsmentioning
confidence: 93%
“…Lifestyle risk factors measured in the study, including current or past smoking, at-risk alcohol consumption, physical inactivity, and overall nutritional inadequacy, are modifiable behaviors and exposures that can raise or lower a person’s risk of diseases [ 25 ]. In addition, those lifestyle risk factors are the key components of the Healthy Promotion Programs by the Korea Ministry of Health and Welfare ( https://www.khealth.or.kr/ ) and associated with depression and/or depressive symptoms in Korean populations [ 26 29 ].…”
Section: Methodsmentioning
confidence: 99%